Stain release type marine antifouling paint with underwater bonding effect
The thiourea-mercapto-modified silicone polymer forms hydrogen bond network and physical crosslinking in marine antifouling coatings, which solves the problem of poor adhesion of silicone coatings and achieves long-term and firm bonding in seawater environments and Excellent anti-fouling performance.
Patent Information
- Application Number
- CN202411250176.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing silicone marine antifouling coatings have poor adhesion and are prone to fall off in water-static environments, which limits their application range.
By preparing thiourea-mercapto-modified siloxane polymer, hydrophobic thiourea groups are introduced to form a hydrogen bond network, and combining thiourea groups to form a stacked physical crosslinking, coordinating the cohesion and adhesion of the polymer, achieving long-term and solid adhesion Knot.
The long-term and firm bonding of the coating is achieved in the seawater environment, maintaining the low surface energy characteristics of the coating surface, ensuring excellent anti-fouling effect and high adhesion.
Smart Images

Figure BDA0005032024940000021 
Figure BDA0005032024940000051 
Figure BDA0005032024940000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of marine antifouling coating technology and underwater coating protection technology, and particularly relates to a functional modified fouling-releasing marine antifouling coating. Background Art
[0002] Marine biofouling generally refers to the process in which marine organisms indiscriminately adhere, grow and accumulate on various substrates immersed in seawater. Since the 1960s, the emergence of organotin marine antifouling coatings has effectively suppressed the harm caused by marine biofouling to the marine industry and made outstanding contributions to the development of the marine industry. However, with the development of science and technology and the improvement of environmental awareness, people have gradually realized that organotin substances can harm the survival of marine organisms, induce genetic mutations in marine organisms, and ultimately enrich through the food chain to endanger human life. In 2008, the International Maritime Organization and countries around the world gradually established complete laws and regulations to prohibit the use of organotin marine antifouling coatings. Therefore, the development of environmentally friendly marine antifouling coatings has become the focus of subsequent research and development in the field of marine antifouling.
[0003] Silicone marine antifouling coatings belong to the field of environmentally friendly fouling-releasing antifouling coatings. Based on lower surface free energy and lower elastic modulus, they utilize the relative movement between the ship and the seawater to achieve the prevention and control of fouling organisms and the removal of loosely adhered fouling organisms, and have great application prospects.
[0004] However, organosilicon marine antifouling coatings currently have poor adhesion to substrates and cannot effectively prevent fouling in static water environments, which urgently need to be improved. In actual use, as the service time increases, or due to friction or collision with other substances, large areas of the coating are very likely to fall off. This shortcoming has greatly limited the promotion and application of low surface energy organosilicon marine antifouling coatings.
[0005] As a "polar hydrophobic" hydrogen bonding motif, thiourea is much less hydrated in an aqueous environment. Since thiourea is hydrophobic, its hydrogen bonding network within the adhesive structure and at the adhesive-target interface is considered to be dehydrated, so the thiourea group can produce strong hydrogen bonding underwater, thereby achieving bonding of related polymers. However, the presence of thiourea groups will lead to increased cohesion of the polymer, and excessive cohesion will inhibit the adhesion of the polymer. Therefore, appropriate design is required to ensure the coordination of the cohesion and adhesion of the polymer, so as to achieve a long-term and strong bonding effect. Summary of the invention
[0006] In order to overcome the problems that the existing organosilicon-based fouling-release marine antifouling coatings have poor adhesion to substrates or intermediate paints, and are easy to fall off during use, and the conventional modification method easily causes the coating surface energy to change, thereby affecting the antifouling performance of the cured coating, the present invention aims to provide a fouling-release marine antifouling coating with underwater bonding effect, by preparing a thiourea-thiol modified siloxane polymer, introducing a hydrophobic thiourea group into the polymer, thereby generating a strong hydrogen bond network effect to achieve a firm bond of the cured coating, and at the same time, the hydration effect of the thiourea group is very low, so the hydrogen bond network formed in the seawater environment has a dehydration effect, so that it can exist for a long time in the seawater environment, providing conditions for the firm bonding of the coating. In addition to the strong hydrogen bond network effect, the coordination of the cohesion and adhesion of the polymer is also the key to the bonding of the cured coating. By introducing a thiol group to form a stacked physical crosslink in the polymer matrix, the influence of the cohesion of the seawater and the polymer on the bonding strength of the coating is minimized, and the coordination and unification of the cohesion and adhesion are achieved, thereby giving full play to the bonding effect of the cured coating. In the finally prepared cured coating, the thiourea-thiol modified siloxane polymer is uniformly mixed with the hydrophobic silicone resin by physical blending. After forming a three-dimensional cross-linked network cured structure, the free thiourea-thiol modified siloxane polymer exists in the gaps of the three-dimensional cross-linked structure, and utilizes the polymer phase separation characteristics to achieve enrichment in the coating-substrate interface area, thereby fully exerting the long-lasting and strong bonding effect in the coating-substrate bonding area, while the coating surface is still a low surface energy methylsiloxane structure, thereby ensuring that the prepared coating still has an excellent anti-fouling effect.
[0007] The present invention is implemented by the following technical solutions:
[0008] In a first aspect, the present invention provides a fouling-release marine antifouling coating with underwater adhesive effect, comprising, by weight: (1) 70 to 100 parts of component A; (2) 10 to 20 parts of component B; (3) 5 to 10 parts of component C;
[0009] in,
[0010] Component A includes by weight:
[0011]
[0012] Component B includes by weight:
[0013] Curing agent 5-10 parts
[0014] Solvent B 20-40 parts;
[0015] Component C includes by weight:
[0016] 1 to 4 parts of catalyst
[0017] Solvent C 5-20 parts;
[0018] The thiourea-mercapto-modified siloxane polymer is prepared by the following steps:
[0019] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, a thiourea compound with an unsaturated group, a mercapto ester monomer, a siloxane polymer, an amine catalyst, and dichloromethane are added in sequence, and then stirred at 20 to 35° C. and 50 to 150 rpm for 6 to 14 hours;
[0020] (2) The product after the reaction is filtered and precipitated, and washed with dichloromethane at least three times, then the precipitated product is obtained by filtering, and dried in a vacuum device for 24 hours to finally obtain a thiourea-mercapto-modified siloxane polymer.
[0021] Preferably, the thiourea compound with an unsaturated group is selected from one of N-allylthiourea, N-propylene N'-2-hydroxyethylthiourea, 4-(3-allylthiourea)benzoic acid, 4-propylenethioamine urea, and 1-allyl-3-(pyridin-2-yl)thiourea.
[0022] Preferably, the mercapto ester monomer is selected from one of 3-mercaptopropionate, trimethylolpropane tris(3-mercaptopropionate), 2-ethylhexyl 3-mercaptopropionate and isooctyl 3-mercaptopropionate.
[0023] Preferably, the siloxane polymer is a methyl vinyl MQ type siloxane resin, whose M:Q value is ≥1.3:1, or the methyl vinyl MQ type silicone resin is liquid at 25°C.
[0024] Preferably, the amine catalyst is selected from one of N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether and N,N,N',N'-tetramethylalkylenediamine.
[0025] Preferably, the weight ratio of the thiourea compound with unsaturated groups, the mercapto ester monomer, the siloxane polymer, the amine catalyst and the dichloromethane is (2-5): (4-8): (10-30); (1-2): (40-80).
[0026] Preferably, the hydrophobic silicone resin is selected from α,ω-dihydroxypolydimethylsiloxane having a viscosity of 2800-10000 mPa·s at 25°C.
[0027] Preferably, the auxiliary agent is selected from at least one of a wetting and dispersing agent, a defoaming agent and a leveling agent.
[0028] Specifically, the wetting and dispersing agent is selected from BYK116, BYK169 of BYK Company, and 901, 903 of Deqian Company.
[0029] Specifically, the defoaming agent is selected from BYK065, BYK066N of BYK Company, and EFKA2020 of Efka of the Netherlands.
[0030] Specifically, the leveling agent is selected from one of German BYK308, BYK310 and BYK373.
[0031] Preferably, the pigment filler is common in the field, and there is no special requirement. As a preferred embodiment, it is selected from but not limited to one of calcium carbonate, ferric oxide, titanium dioxide, barium sulfate, kaolin, and zinc oxide.
[0032] Preferably, the solvent A is selected from one of methanol, xylene and acetone.
[0033] Preferably, the curing agent is selected from one of tetraethyl orthosilicate, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(isomethacryloyloxy)propyltrimethoxysilane and γ-methacryloyloxypropyltriisopropoxysilane.
[0034] Preferably, the solvent B is selected from one of acetone, butanone and acetylacetone.
[0035] Preferably, the catalyst is selected from dibutyltin diosilicate, stannous octoate, and organic bismuth.
[0036] Preferably, the solvent C is selected from one of acetylacetone, cyclohexanone and toluene.
[0037] In a second aspect, the present invention further provides a method for preparing the coating according to the first aspect, which can be prepared in a conventional manner. First, component A, component B, and component C are prepared separately and sealed and stored. When coating, components A, B, and C are mixed in a conventional mixing manner and immediately coated, which specifically comprises the following steps:
[0038] (1) Add thiourea-mercapto-modified siloxane polymer, hydrophobic silicone resin, auxiliary agent, and 50% solvent A to a dispersing and stirring device in sequence, and then disperse at 100 rpm for 20 min. Then, add pigments and fillers and 50% solvent A to the dispersing and stirring device, and continue to disperse at the same speed for 20 min to prepare component A, and then seal and store;
[0039] (2) using a dispersing and stirring device to disperse the curing agent and solvent B at 50 rpm for 10 min, i.e., preparing component B, and then sealing and storing;
[0040] (3) The catalyst and solvent 3 were dispersed at 50 rpm for 10 min using a dispersing and stirring device to prepare component C, which was then sealed and stored.
[0041] In the third aspect, the present invention also provides an antifouling coating prepared by the coating described in the first aspect, wherein component A, component B, and component C are evenly mixed using conventional dispersion processes and equipment, and applied by spraying, rolling, brushing, etc., and cured for at least 48 hours to prepare a coating with a film thickness of 150 to 250 um.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] 1. The coating is prepared by synthesizing thiourea-mercapto-modified siloxane polymers and blending them with hydrophobic silicone resins. After curing, the free thiourea-mercapto-modified siloxane polymers will be enriched in the contact area between the coating and the substrate, thereby achieving a long-lasting and strong bonding effect. At the same time, the coating surface still maintains excellent low surface energy characteristics and maintains an anti-fouling effect.
[0044] 2. Introducing thiourea groups into modified siloxane polymers, giving full play to the low hydration effect of the thiourea groups and the resulting hydrogen bond network effect, thereby achieving the adhesion and long-term effectiveness of the polymer, and ensuring effective adhesion of the coating in the final cured coating.
[0045] 3. Introduce mercapto groups into modified siloxane polymers to form stacked physical crosslinks in the polymer matrix, thereby minimizing the effect of seawater and polymer cohesion on the coating bonding strength, achieving the coordination and unification of cohesion and adhesion, and thus bringing out the bonding effect of the modified siloxane polymer to avoid polymer breakage due to excessive cohesion, thereby affecting the bonding of the cured coating.
[0046] 4. The synthesis of thiourea-mercapto-modified siloxane polymers promotes the formation of cross-linked structures through Michael addition reaction, which can achieve the reaction without excessive external energy, thus facilitating industrial application and reducing production difficulty. DETAILED DESCRIPTION
[0047] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, without departing from the concept of the present invention, several variations and improvements can be made. These all belong to the protection scope of the present invention.
[0048] The coating of the present invention is characterized by synthesizing a thiourea-thiol modified siloxane polymer, utilizing the thiol group to achieve the coordination and unification of the polymer's cohesive force and adhesive force, utilizing the thiol group to achieve a long-lasting hydrogen bond network of the polymer in seawater, and finally achieving a long-lasting and firm bonding effect. In addition, by synthesizing a thiourea-thiol modified siloxane polymer and blending it with a hydrophobic silicone resin to prepare the coating, the free thiourea-thiol modified siloxane polymer after curing will be enriched in the contact area between the coating and the substrate, thereby achieving a long-lasting and firm bonding effect, while the coating surface still maintains excellent low surface energy characteristics and maintains an antifouling effect.
[0049] The raw materials used in the examples are shown in Table 1. The specific implementation is not limited to the raw materials in Table 1, and corresponding products can be selected according to the above. Other raw materials used in the examples are all commercially available chemical reagents.
[0050] Table 1
[0051]
[0052]
[0053] Thiourea-mercapto-modified siloxane polymer 1
[0054] The weight ratio of the thiourea compound with unsaturated groups, the mercapto ester monomer, the siloxane polymer, the amine catalyst, and the dichloromethane is 5:4:30; 2:70. The specific preparation process is as follows:
[0055] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, a thiourea compound 1-1 having an unsaturated group, a mercapto ester monomer 2-3, a siloxane polymer 3-1, an amine catalyst 4-1, and dichloromethane are added in sequence, and then stirred at 25° C. and 50 rpm for 12 h;
[0056] (2) The product after the reaction is filtered and precipitated, and washed with dichloromethane at least three times, then the precipitated product is obtained by filtering, and dried in a vacuum device for 24 hours to finally obtain a thiourea-mercapto-modified siloxane polymer.
[0057] Thiourea-mercapto-modified siloxane polymer 2
[0058] The weight ratio of the thiourea compound with unsaturated groups, the mercapto ester monomer, the siloxane polymer, the amine catalyst, and dichloromethane is 2:7:10; 1.5:40. The specific preparation process is as follows:
[0059] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, a thiourea compound 1-2 having an unsaturated group, a mercapto ester monomer 2-1, a siloxane polymer 3-1, an amine catalyst 4-2, and dichloromethane are added in sequence, and then stirred at 20° C. and 100 rpm for 14 hours;
[0060] (2) The product after the reaction is filtered and precipitated, and washed with dichloromethane at least three times, then the precipitated product is obtained by filtering, and dried in a vacuum device for 24 hours to finally obtain a thiourea-mercapto-modified siloxane polymer.
[0061] Thiourea-mercapto-modified siloxane polymer 3
[0062] The weight ratio of the thiourea compound with unsaturated groups, the mercapto ester monomer, the siloxane polymer, the amine catalyst, and dichloromethane is 4:8:20; 1:80. The specific preparation process is as follows:
[0063] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, a thiourea compound 1-3 having an unsaturated group, a mercapto ester monomer 2-2, a siloxane polymer 3-2, an amine catalyst 4-2, and dichloromethane are added in sequence, and then stirred at 35° C. and 150 rpm for 6 hours;
[0064] (2) The product after the reaction is filtered and precipitated, and washed with dichloromethane at least three times, then the precipitated product is obtained by filtering, and dried in a vacuum device for 24 hours to finally obtain a thiourea-mercapto-modified siloxane polymer.
[0065] Examples 1-5
[0066] The proportions of the three components A, B, and C of Examples 1-5 are shown in Table 2, and the specific proportions of the components of Examples 1-5 are shown in Table 3.
[0067] Table 2
[0068] Components Example 1 Example 2 Example 3 Example 4 Example 5 A 70 80 100 90 70 B 10 15 20 15 20 C 6 5 10 10 5
[0069] Table 3
[0070]
[0071] According to Table 2 and Table 3, the preparation method of the fouling-releasing marine antifouling coating with underwater adhesion effect of Examples 1-5 is as shown in the following steps:
[0072] (1) Add thiourea-mercapto-modified siloxane polymer, hydrophobic silicone resin, auxiliary agent, and 50% solvent A to a dispersing and stirring device in sequence, and then disperse at 100 rpm for 20 min. Then, add pigments and fillers and 50% solvent A to the dispersing and stirring device, and continue to disperse at the same speed for 20 min to prepare component A, and then seal and store;
[0073] (2) using a dispersing and stirring device to disperse the curing agent and solvent B at 50 rpm for 10 min, i.e., preparing component B, and then sealing and storing;
[0074] (3) using a dispersing and stirring device to disperse the catalyst and solvent 3 at 50 rpm for 10 min, i.e., preparing component C, and then sealing and storing;
[0075] (4) Component A, component B, and component C are mixed uniformly using conventional dispersion processes and equipment, and applied by spraying, rolling, brushing, etc. After curing for at least 48 hours, a coating with a film thickness of 150 to 250 μm is prepared.
[0076] In actual application, the antifouling coating can be prepared by conventional methods of marine antifouling coatings, and is not limited to the above preparation method.
[0077] Comparative Example 1 (Ordinary silicone low surface energy marine antifouling coating)
[0078] The common organosilicon low surface energy marine antifouling paint comprises the following raw materials in parts by weight: 90.0 parts of polysiloxane resin, 30.0 parts of pigments and fillers, 4.0 parts of cross-linking curing agent, 1.5 parts of catalyst, 0.5 parts of auxiliary agent and 10.0 parts of third solvent.
[0079] The polysiloxane resin is α, ω-dihydroxy polydimethylsiloxane with a viscosity of 10000 mPa·s; the pigment is zinc oxide; the cross-linking curing agent is tetraethyl orthosilicate; the catalyst is dibutyltin disilicate; the auxiliary agent is 0.5 parts of BYK161 dispersant from BYK; and the third solvent is xylene.
[0080] (1) 90.0 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 10000 mPa·s and 30.0 parts of micron-sized zinc oxide were added to a disperser and dispersed at 300 rpm for 30 min. Subsequently, 0.5 parts of BYK161 dispersant from BYK was added to the disperser at 200 rpm and dispersed for 30 min. The mixture was then ground with a sand mill to a fineness of less than 40 μm to prepare a pre-dispersed slurry and canned for standby use.
[0081] (2) 4.0 parts of tetraethyl orthosilicate and 10.0 parts of xylene were mixed evenly to prepare a crosslinking curing agent component, which was then canned for standby use; 1.5 parts of dibutyltin dioxysilicate and 20.0 parts of xylene were mixed evenly to prepare a catalyst component, which was then canned for standby use;
[0082] (3) Before use, the pre-dispersed slurry, the cross-linking curing agent component, and the catalyst component are stirred uniformly according to the ratio. After the obtained coating is applied and cured, a common organic silicon low surface energy marine antifouling coating with a thickness of 150 to 250 μm is obtained.
[0083] Comparative Example 2
[0084] Compared with Example 1, no mercapto ester monomer is introduced into the prepared modified polysiloxane polymer, the remaining components and their weight parts are the same, and the preparation process is also the same as that of Example 1.
[0085] <Specific test experiments and conditions>
[0086] Test 1: Surface Free Energy
[0087] The contact angles of deionized water and diiodomethane on the surface of the cured coating were measured using the XG-CAMC3 fully automatic contact angle meter produced by Shanghai Xuanzhun Instrument Co., Ltd. Before the measurement, the coating surface needs to be cleaned with anhydrous ethanol and dried, and then the surface free energy of the coating is calculated according to the Owens two-liquid method.
[0088] Test 2: Pull-off method to measure adhesion after 100 days of seawater immersion (steel plate, epoxy intermediate paint)
[0089] The BGD500 digital semi-automatic adhesion tester produced by Guangzhou Biaogeda Precision Instrument Co., Ltd. was used to measure the adhesion of the coating applied on the corresponding substrate or epoxy intermediate paint. The steel plate needs to be polished with 800-grit sandpaper before use, and the epoxy intermediate paint used is the epoxy micaceous iron intermediate paint produced by Shanghai Jinsi Di. Before the test, it needs to be immersed in sterilized seawater for 100 days, and then taken out and dried for testing.
[0090] Test 3: Antifouling performance
[0091] A suspension containing at least 108 units of Streptococcus salivarius was dispersed in 20 ml of tryptic soy broth and incubated at 38°C, 5% CO2 for 2 hours. The suspension was then further diluted and inoculated in agar supplemented with 5% sheep blood and incubated at 38°C, 5% CO2 for 48 hours, and then the units containing six colonies were dispersed in 10 ml of tryptic soy broth. Subsequently, 20 ml of the above bacterial suspension was covered on the coating of 10×5 cm area and incubated at 38°C, 5% CO2 for 24 hours. After the incubation, each sample needed to be rotated and rinsed in 45 ml of distilled water for 30 seconds, and then rinsed with 50 ml of distilled water to remove non-sticky materials. The surface-adherent bacteria were observed using a Simga300 scanning electron microscope produced by Carl Zeiss, Germany.
[0092] The specific test results of Examples 1-5 and Comparative Examples 1-2 are shown in Table 4.
[0093] Table 4
[0094]
[0095] The above tests confirm that the coatings of the examples and the comparative examples have lower surface free energy, thus exhibiting excellent antifouling performance. The advantage of the present invention is that the examples have excellent adhesion on various polar substrates, which is much stronger than the comparative examples, and exhibits excellent bonding effect.
[0096] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A fouling-releasing marine antifouling coating with underwater adhesive effect, It is characterized in that In parts by weight, it comprises: (1) 70 to 100 parts of component A; (2) 10 to 20 parts of component B; (3) 5 to 10 parts of component C; in, Component A includes by weight: Component B includes by weight: Curing agent 5-10 parts Solvent B 20-40 parts; Component C includes by weight: 1 to 4 parts of catalyst Solvent C 5-20 parts; The thiourea-mercapto-modified siloxane polymer is prepared by the following steps: (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, a thiourea compound with an unsaturated group, a mercapto ester monomer, a siloxane polymer, an amine catalyst, and dichloromethane are added in sequence, and then stirred at 20 to 35° C. and 50 to 150 rpm for 6 to 14 hours; (2) The product after the reaction was filtered and precipitated, and washed with dichloromethane at least three times, and then the precipitated product was obtained by filtration, and dried in a vacuum device for 24 hours to obtain a thiourea-mercapto-modified siloxane polymer.
2. The antifouling coating according to claim 1, It is characterized in that The thiourea compound with an unsaturated group is selected from one of N-allylthiourea, N-propylene N'-2-hydroxyethylthiourea, 4-(3-allylthiourea)benzoic acid, 4-propylenethioamine urea, and 1-allyl-3-(pyridin-2-yl)thiourea.
3. The antifouling coating according to claim 1, It is characterized in that The mercapto ester monomer is selected from one of 3-mercaptopropionate, trimethylolpropane tris(3-mercaptopropionate), 2-ethylhexyl 3-mercaptopropionate and isooctyl 3-mercaptopropionate.
4. The antifouling coating according to claim 1, It is characterized in that The silicone polymer is selected from methyl vinyl MQ type silicone resin, whose M:Q value is ≥1.3:1, or the methyl vinyl MQ type silicone resin is liquid at 25°C.
5. The antifouling coating according to claim 1, It is characterized in that The amine catalyst is selected from one of N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether and N,N,N',N'-tetramethylalkylenediamine.
6. The antifouling coating according to claim 1, It is characterized in that The weight ratio of the thiourea compound with unsaturated groups, the mercapto ester monomer, the siloxane polymer, the amine catalyst and the dichloromethane is (2-5): (4-8): (10-30); (1-2): (40-80).
7. A method for preparing an antifouling coating according to any one of claims 1 to 6, It is characterized in that The steps include: (1) Add thiourea-mercapto-modified siloxane polymer, hydrophobic silicone resin, auxiliary agent, and 50% solvent A to a dispersing and stirring device in sequence, and then disperse at 100 rpm for 20 min. Then, add pigments and fillers and 50% solvent A to the dispersing and stirring device, and continue to disperse at the same speed for 20 min to prepare component A, and then seal and store; (2) using a dispersing and stirring device to disperse the curing agent and solvent B at 50 rpm for 10 min, i.e., preparing component B, and then sealing and storing; (3) The catalyst and solvent 3 were dispersed at 50 rpm for 10 min using a dispersing and stirring device to prepare component C, which was then sealed and stored.
8. An antifouling coating prepared by the antifouling coating according to any one of claims 1 to 6, It is characterized in that Component A, component B and component C are mixed evenly, applied on the substrate, and cured for at least 48 hours to prepare a coating with a film thickness of 150 to 250 um.
Citation Information
Patent Citations
Low-surface-energy organosilicone marine antifouling coating
CN114015320A
Preparation method of organic fluorine / silicon modified polythionocarbamate antifouling paint
CN114539897A
Hydrogen bond-bonded modified organic silicon marine antifouling paint
CN117363135A
